NEUTROPHIL LYMPHOCYTE RATIO IN DIAGNOSIS OF STROKE TYPE IN MOHAMMAD HOESIN HOSPITAL PALEMBANG - Apriyanto Apriyanto; Bahar E; Ramadhon P D; Marisdina S; Junaidi A (Sriwijaya University Learning and Education International Conference, 2018)
Background and aims: Stroke is a disease of acute focal and global functional brain disorder due to blood flow occlusion to the brain. Disorder of blood brain barrier may trigger leukocyte infiltration and release of proinflammatory cytokines following an acute ischaemic stroke. CT-scan is the gold standard for diagnosing stroke which is not available yet in remote areas in Indonesia. This research aims to indentify the diagnostic value of neutrophil and lymphocyte ratio in order to determine stroke type (hemorrhagic and non hemmorrhagic). Method: this diagnostic test research was conducted in the inpatients ward of Neurology Departement of Dr Mohammad Hoesin Hospital in Palembang from August 2017 to November 2017. The number of samples in this research that meet the inclusion criteria and exclusion criteria were 228 samples. The frequency and distribution of the data are explained through tables and figures and the cut point of N/L ratio are analyzed by ROC curve and the sensitivity and specificity value is obtained based on the N/L cut point. Analysis of the data was conductedusing SPSS22.0version. Results: This research shows that there is no difference on the age range, sex, and onset of the disease in patients with stroke hemorrhagic and non hemorrhagic (p>0.05). Based on ROC analysis, cut point of N/L ratio is 3.14 with AUC value 0.764 (0.701-0,826). Based on the cutting point value to determine classification of hemorrhagic and non hemorrhagic stroke, the sensitvity value is 72.99%, specificity 75.82%, positive predictive value (PPV) 82%, and negativepredictivevalue(NPV)65.1%. Conclusion: Ratio of N/L with cut point value 3.414 has sensitivity 72.99% and specificity 75.82%